Influence of Brand Ambassador Heart2heart Towards Consumers' Purchase Decisions for Barenbliss Products Generation Z in Denpasar City - Widiantari, Ni Komang; Putra, I Komang Trisna Eka; Pratiwi, Anak Agung Neva Eka (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The rapid growth of the beauty industry encourages companies to implement innovative marketing strategies to attract consumers, especially Generation Z who are highly active on social media. One strategy widely used in modern marketing is the utilization of brand ambassadors to strengthen brand image and influence consumer purchasing decisions. This study aims to analyze the influence of the Heart2Heart brand ambassador on purchasing decisions for Barenbliss products among Generation Z consumers in Denpasar City.This study employed a quantitative approach with a descriptive method. The sample consisted of 100 respondents selected using purposive sampling with criteria including consumers aged 17–26 years who have used Barenbliss products and are aware of Heart2Heart as the brand ambassador. Data were collected through questionnaires using a Likert scale. The brand ambassador variable was measured through indicators of credibility, attractiveness, and influence power, while the purchasing decision variable was measured through the stages of need recognition, information search, evaluation of alternatives, purchase decision, and post-purchase behavior. The results show that the Heart2Heart brand ambassador has a positive influence on purchasing decisions for Barenbliss products among Generation Z consumers in Denpasar City. This is indicated by the high level of respondent agreement regarding the credibility, attractiveness, and influence of the brand ambassador, which increases consumer interest and purchasing decisions. Therefore, the use of a credible and attractive brand ambassador can be an effective marketing strategy to influence consumer purchasing decisions.